Simultaneous Quantification of 20 Synthetic Cannabinoids and 21 Metabolites, and Semi-quantification of 12 Alkyl Hydroxy Metabolites in Human Urine by Liquid Chromatography-Tandem Mass Spectrometry - Scheidweiler, Karl B. (2013)
Clandestine laboratories constantly produce new synthetic cannabinoids to circumvent legislative efforts, complicating toxicological analysis. No extensive synthetic cannabinoid quantitative urinary methods are reported in the literature. We developed and validated a liquid chromatography tandem mass spectrometric (LC-MS/MS) method for simultaneously quantifying JWH-018, JWH-019, JWH-073, JWH-081, JWH-122, JWH-200, JWH-210, JWH-250, JWH-398, RCS-4, AM-2201, MAM-2201, UR-144, CP 47,497-C7, CP 47,497-C8 and their metabolites, and JWH-203, AM-694, RCS-8, XLR-11 and HU-210 parent compounds in urine. Non-chromatographically resolved alkyl hydroxy metabolite isomers were considered semi-quantitative. β-glucuronidase hydrolyzed urine was extracted with 1 ml Biotage SLE+ columns. Specimens were reconstituted in 150 µL mobile phase consisting of 50% A (0.01% formic acid in water) and 50% B (0.01% formic acid in 50:50 methanol:acetonitrile). 4 and 25 µL injections were performed to acquire data in positive and negative ionization modes, respectively. The LC-MS/MS instrument consisted of a Shimadzu UFLCxr system and an ABSciex 5500 Qtrap mass spectrometer with an electrospray source. Gradient chromatographic separation was achieved utilizing a Restek Ultra Biphenyl column with a 0.5 ml/min flow rate and an overall run time of 19.5 and 11.4 min for positive and negative mode methods, respectively. Quantification was by multiple reaction monitoring with CP 47,497 compounds and HU-210 ionized via negative polarity; all other analytes were acquired in positive mode. Lower and upper limits of linearity were 0.1–1.0 and 50–100 µg/l (r2 > 0.994). Validation parameters were evaluated at three concentrations spanning linear dynamic ranges. Inter-day analytical recovery (bias) and imprecision (N=20) were 88.3–112.2% and 4.3–13.5% coefficient of variation, respectively. Extraction efficiencies and matrix effect (N=10) were 44–110 and −73 to 52%, respectively. We present a novel LC-MS/MS method for simultaneously quantifying 20 synthetic cannabinoids and 21 metabolites, and semi-quantifying 12 alkyl hydroxy metabolites in urine.